A military airport location selection by AHP integrated PROMETHEE and VIKOR methods - SENNAROĞLU, BAHAR (PERGAMON-ELSEVIER SCIENCE LTD, 2018)
This paper presents a location selection problem for a military airport using multiple criteria decision making methods. A real-world decision problem is presented and the decision criteria to evaluate alternative locations are specified. The objective is to identify the best location among candidate locations. Nine main criteria and thirty-three sub-criteria are identified by taking into account not only requirements for a military airport such as climate, geography, infrastructure, security, and transportation but also its environmental and social effects. The criteria weights are determined using AHP. Ranking and selection processes of four alternatives are carried out using PROMETHEE and VIKOR methods. Furthermore, the results of PROMETHEE and VIKOR methods are compared with the results of COPRAS, MAIRCA and MABAC methods. All methods suggest the same alternative as the best and produce the same results on the rankings of the location alternatives. One-way sensitivity analysis is carried out on the main criteria weights for all methods. Statistically significant correlations are observed between the rankings of the methods. Therefore, it is concluded that PROMETHEE, VIKOR, COPRAS, MAIRCA and MABAC methods can be successfully used for location selection problems and in general, for other types of multi criteria decision problems with finite number of alternatives.
Keywords: Location selection; Multiple criteria decision making; AHP; PROMETHEE; VIKOR; MULTICRITERIA DECISION-ANALYSIS; SITE SELECTION; CONSTRUCTION; PERFORMANCE; PLANT